Aplikatif Manajemen Pendidikan dalam Pembentukan Karakter Santri: Studi PP. Sirojul Hasan Klenang Kidul Probolinggo - Rizqi Fauziyah; Nanang Qosim (At- Ta'lim : Jurnal Pendidikan, 2020)
Students character education planning is carried out by boarding school (kyai) caregivers, educator, and the preparation of the determination of needs, program design, regarding targets/targets, location, time and program applications in the entity. Managing and caring for educational sarpras is a shared responsibility, starting from the caregiver of boarding school (kyai), the asatidz-asatidzah, santri, committees and neighboring pesantren. Coordination of the development of santri character education is carried out in guidance with appropriate educator. application of students through various learning models, habituation, exemplary/role models, civilizing discipline (discipline culture), tazkiyyatun annafsi (self-cleansing, soul and heart), motivation and order Assessment of character education can be through examinations written, report cards, behavior (good morals), sympathizers, graduates, and public.